Model Kepuasan Pelanggan di PT Mediacomm Citra Perdana - Roy Dharma Muliawan; Ma'mun Sarma; Soewarno T Soekarto (Institut Pertanian Bogor, 2016)
To achieved customer satisfaction, therefore the performance and quality service must be employed according to the standard. PT Mediacomm Citra Perdana is a company engaged in the communication sector with focusing on advertising. Competition is inevitable for PT. Mediacomm Citra Perdana while looking prospective client and advertise its task. Work culture while also serve as tradition but also play an important role in the terms of speed, accurate and professionalism. The study of Model of Customer Satisfaction in PT Mediacomm Citra Perdana is purposely conducted for: (1) To Identify Customer Perception; (2) To analyze the Effect of Product Quality; (3) To Identify Variables that Influenced Quality Products, Services and Marketing Power (in terms of Management) by PT Mediacomm Citra Perdana. The data collected by secondary data of using survey data with Likert scale to describe the characteristics of the consumer, the service and quality of the process (frequency, mean, percentage of cross tabulation, the average scores). Multiple linear regression are also used to analyze the influence of quality attributes on customer satisfaction. The data are also used for test the validity and the reliability. The characteristics of the clients are processed with Contigency Table and Spearman Rank Correlation. The assessment of importance level and customer expectation is analyzed with Importance Performance Analysis. For overall satisfaction of customer with regards to product/service attribute analyzed with Customer Satisfaction Index (CSI). Validity result shows 14 valid attribute on reality-dimension while the other 20 is invalid on reality-dimension. On the expectation-dimensions, 23 attribute are recorded its validiy while the other 11 attribute in invalid. Correlation test shows, the three independent variables correlated with the dependent variable with a correlation coefficient > 0,4. Multiple regression shows, three independent variables explained > 50% change in the dependent variable. Customer Satisfaction Index are at level 76,84%. Based on the calculation, CSI result on 0,768 indicate the satisfaction level index are positioned in the range 0,66-0,88 which means PT. Mediacomm Citra Perdana gives excellent performance.